The Discrepancy of Parents’ Theories of Intelligence and Parental Involvement - Jiang, Kexin; Liu, Juan; Liu, Chunhui; Guo, Xiaolin; Zhou, Huan; Lv, Bo; Liu, Zhaomin; Luo, Liang (Frontiers in Psychology, 2019)
In families, mothers and fathers may hold the same or different levels of theories of intelligence. This congruence and discrepancy may influence parental involvement in children’s education. The current study examined how both parents’ theories of intelligence and the direction and degree of the discrepancy of parents’ intelligence theories influence maternal and paternal involvement separately. We measured 1,694 matched pairs of parents’ theories of intelligence and educational involvement, and examined the relationships using linear regressions and polynomial regressions with response surface analysis. The results showed that 1) the mother’s intelligence theory positively related to both paternal involvement and maternal involvement, but the father’s intelligence theory only positively related to paternal involvement; 2) when the parents’ theories of intelligence reached congruence, the parents’ theories of intelligence are positively related to both maternal and paternal involvement; 3) when the parents’ theories of intelligence have discrepancy, the maternal involvement is higher while the mother’s intelligence theory’s level is more incremental than father’s; and 4) when the parents’ theories of intelligence have discrepancy, more discrepancy of parents’ theories of intelligence is related to more paternal involvement. This study revealed the significance of mother’s role in education, highlighted the importance of parents’ congruence and discrepancies in beliefs, examined how parents’ beliefs impact their own behavior and their couple’s behavior.